FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN USAHATANI KOPI ARABIKA KELOMPOK TANI SARI MEKAR DI DESA TAMBAKAN, KECAMATAN KUBUTAMBAHAN, KABUPATEN BULELENG - Oswaldus Saldiman; Nyoman Yudiarini; Luh Putu Kirana Pratiwi (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2021)
This research aims to determine how the income level of Arabica coffee is, as well as to find out what factors affect the income of Arabica coffee farmers in Tambakan Village, Kubutambahan District, Buleleng Regency. The location of this study was determined intentionally or purposively. The method used in this research is a survey method with a sample of the whole population so that it uses the census method. The results of the study showed that the income of Arabica coffee farming in Tambakan Village, Kubutambahan District, Buleleng Regency was IDR 52,420,096 with a total income of IDR 62,760,000 and a total production cost of IDR 10,339,905. and income factors that have a significant effect, namely significantly influence the increase or decrease in its use, are production factors, selling price factors, and production cost factors, while the land area and production capital factors do not have a significant effect on Arabica coffee farming in Tambakan Village, Kubutambahan District. , Buleleng Regency.